Medicinal plants as a possibility of care for urinary disorders - Andrieli Daiane Zdanski de Souza; Marjoriê da Costa Mendieta; Teila Ceolin; Rita Maria Heck (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210377 Aims: to investigate the medicinal plants recommended for urinary disorders, by descendents of the rural area of a town in the southern region of Rio Grande do Sul (RS). Method: qualitative research with nine participants from the rural area of the town Capão do Leão/RS. Data collection occurred between July and August of 2010 through simple observation and semi-structured interviews, which were compared with scientific studies. Results: seven plants for urinary disorders were listed by the participants (Bauhinia sp., Bidens alba, Equisetum hyemale, Fragaria vesca, Petroselium crispum, Phyllanthus sp., Plantago australis). Scientific studies about all of them were found, demonstrating their popularly known effects. Conclusions: It is important to know and value the popular knowledge about medicinal plants, as well as their scientific evidences in order to assist health professionals in their work.